Identifikasi Sesar Sumatra Segmen Manna Menggunakan Data Anomali Gravitasi GGMplus dengan Metode Second Vertical Derivative (SVD) - Arezzo Fabio Fentola Parinus Frezo Leni Ikhwandi; Arif Ismul Hadi; Hilmi Zakariya; Refrizon Refrizon (Universitas Andalas, 2023)
This study uses the gravity method to assess the characteristics of the Manna segment fault, a part of the Sumatran fault. This research aims to contribute to the existing knowledge by providing additional insights into the fault's characteristics, which is essential for future disaster mitigation efforts. The Manna segment fault is geographically situated between coordinates 4.4⁰S - 3.9⁰ S and 102.7⁰ E – 103.2⁰ E, making this area prone to earthquake hazards. The gravity anomaly data, including free air and topography, were collected from 62,501 data points. The Simple Bouguer Anomaly (SBA) values obtained ranged from 25 mGal to 95 mGal. By utilizing the Second Vertical Derivative (SVD) method and dividing the study area into three regions with multiple sections, the analysis revealed that the minimum and maximum SVD values were relatively similar. This suggests that the Manna fault can be classified as a strike-slip fault, with SVD values ranging from Elkins-20 mGal to 6 mGal. The study identified branches of the main fault in regions 2 and 3 based on the SVD map. Overall, this study enhances our understanding of the Manna segment fault, providing valuable insights into its characteristics and contributing to future disaster mitigation efforts.